2011
DOI: 10.1007/s13149-010-0128-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigations entomologiques menées autour de dix cas de fièvre jaune survenus en 2009 dans la région sanitaire du Denguélé, Côte-d’Ivoire

Abstract: In November 2009, ten suspicious cases of yellow fever, including six deaths, were notified in the region of Denguélé, in the northwest of Côte-d'Ivoire. In order to evaluate the extent of yellow fever virus circulation and the risk for local people, a mission of entomological investigation was carried out by the Ministry of Health and Public Hygiene of Côte-d'Ivoire. Entomological investigations were conducted in the villages of confirmed cases (Banakoro and Tron-Touba) and the centers of consultation and hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(3 reference statements)
0
3
0
1
Order By: Relevance
“…However, the sudden decline of Aedes spp. numbers in October 2013 in the urban setting might be due to heavy precipitations and exacerbated flushing of their eggs because of the lack of protective vegetation in the built-up environment [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the sudden decline of Aedes spp. numbers in October 2013 in the urban setting might be due to heavy precipitations and exacerbated flushing of their eggs because of the lack of protective vegetation in the built-up environment [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that A. aegypti colonizes practically all kinds of containers in the immediate environment of humans, particularly water storage ones. These containers, which constitute the main breeding sites for this vector (Konan et al, 2011; Koné et al, 2013; Tezzo et al, 2021), are constantly used by the population of Abidjan to store water because of the inadequacy of the water supply network to serve a continuously growing population (Office National de l'Eau Potable, 2017). After water storage containers used tires represented the second most important category of breeding sites in terms of frequency.…”
Section: Discussionmentioning
confidence: 99%
“…In Côte d'Ivoire, after the first case of dengue virus serotype 3 in 2008 (World Health Organization [WHO], 2009), several other studies have reported the presence of this arbovirus in the country (Akoua‐Koffi et al, 2011; Aoussi et al, 2014; L'Azou et al, 2015; Moi et al, 2010; WHO, 2017). The country has also known since 2008, a resurgence of yellow fever (Attoh‐Touré et al, 2010; Konan et al, 2009) and Zika was also reported (Akoua‐Koffi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…En 2008, la ville d' Abidjan a été confrontée à une épidémie de fièvre jaune après celle de 2001 [4]. En 2009, dix cas dont sept suspects et trois détectés positifs ont été notifiés dans les districts sanitaires de Minignan et d'Odienné au Nord-Ouest du pays [5]. L'année suivante, trois cas positifs aux IgM antiamaril et décédés ont été notifiés dans le district sanitaire de Séguéla.…”
Section: Introductionunclassified